Aneurysmal bone cyst inadvertently treated with chemotherapy—A series of three cases. Issue 10 (6th August 2020) - Deventer, Niklas; Deventer, Nils; Gosheger, Georg; Budny, Tymoteusz; de Vaal, Marieke; Riegel, Arne; Heitkoetter, Birthe; Kessler, Torsten; Poeppelmann, Monika; Rossig, Claudia; Juergens, Heribert; Luebben, Timo
Abstract: Aneurysmal bone cyst (ABC) is a benign locally aggressive tumor that occurs in childhood and early adulthood. Most relevant differential diagnoses are the telangiectatic osteosarcoma and the giant cell tumor. In the present case series chemotherapy following the EURAMOS or the Euro‐Ewing 99 protocol was externally applied in three patients with the misdiagnosis of ABC as malignant bone tumor. In all three cases, a significant reduction of the volume of the ABC was achieved. This is the first report about the use of neoadjuvant chemotherapy in ABC. Chemotherapy reduces the size of an ABC and leads to progressive sclerosis.